Crawford's Beethoven statue for the music hall in Boston - Crawford, Thomas, 1814-1857 (sculptor):::Creator:::::::::::: (Leipzig; Germany)
Fanciful drawing of Thomas Crawford's bronze statue of Beethoven, which is now located at the New England Conservatory of Music.